2016
DOI: 10.1016/j.neuron.2016.04.032
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Form of Local Plasticity in Tuft Dendrites of Neocortical Somatosensory Layer 5 Pyramidal Neurons

Abstract: Tuft dendrites of layer 5 pyramidal neurons form a separate biophysical and processing compartment. Presently, little is known about plasticity mechanisms in this isolated compartment. Here, we describe a novel form of plasticity in which unpaired low-frequency (0.1 Hz) stimulation of tuft inputs resulted in prolonged transient (86.3 ± 7.3 min) potentiation of EPSPs (286.1% ± 30.5%) and enhanced local excitability that enabled more-efficient back-propagation of axo-somatic action potentials and dendritic calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 75 publications
5
36
0
Order By: Relevance
“…In this study, we did not consider various other plasticity mechanisms: intrinsic and homeostatic plasticity [Triesch, 2007, Turrigiano, 2011, Turrigiano, 2012, Yger and Gilson, 2015, structural plasticity [Caroni et al, 2012], heterosynaptic plasticity [Chistiakova et al, 2014, Chistiakova et al, 2015 and branch strength plasticity [Losonczy et al, 2008, Makara et al, 2009, Legenstein and Maass, 2011. Moreover, we only considered basal dendrites, and different learning rules might be present in apical tuft dendrites [Kim et al, 2015, Sandler et al, 2016, especially in cortical layer 5 pyramidal neurons which are known to possess a powerful calcium spike initiation zone in this region [Schiller et al, 1997]. Understanding how this spike interacts with plasticity could provide further insight into the interaction of bottom-up inputs arriving on the basal dendrites and top-down feedback arriving at the tuft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not consider various other plasticity mechanisms: intrinsic and homeostatic plasticity [Triesch, 2007, Turrigiano, 2011, Turrigiano, 2012, Yger and Gilson, 2015, structural plasticity [Caroni et al, 2012], heterosynaptic plasticity [Chistiakova et al, 2014, Chistiakova et al, 2015 and branch strength plasticity [Losonczy et al, 2008, Makara et al, 2009, Legenstein and Maass, 2011. Moreover, we only considered basal dendrites, and different learning rules might be present in apical tuft dendrites [Kim et al, 2015, Sandler et al, 2016, especially in cortical layer 5 pyramidal neurons which are known to possess a powerful calcium spike initiation zone in this region [Schiller et al, 1997]. Understanding how this spike interacts with plasticity could provide further insight into the interaction of bottom-up inputs arriving on the basal dendrites and top-down feedback arriving at the tuft.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increasing number of experimental studies have revealed plasticity mechanisms which do not rely on postsynaptic action potential generation, but instead on local postsynaptic dendritic spikes [Golding et al, 2002, Gordon et al, 2006, Gambino et al, 2014, Brandalise and Gerber, 2014, Kim et al, 2015, Cichon and Gan, 2015 or subthreshold events for dendritic spikes [Weber et al, 2016, Sandler et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…NMDA spikes are known to be involved in facilitating long term potentiation (LTP) and depression (LTD) (Gambino et al 2014;Sandler et al 2016;Gordon et al 2006;Brandalise et al 2016;Golding et al 2002). We showed in Figure 6 that precisely timed inhibition could gradually reduce the NMDA-dependent current influx by up to 60% of its original charge simultaneously in a group of spines cooperatively involved in generating the NMDA spike.…”
Section: Dendritic Inhibition Controlling Nmda-induced Plasticity In mentioning
confidence: 98%
“…It has been shown that dendritic Na + -, Ca 2+ -and NMDA-spikes can implement a variety of computational functions, including input pattern classifications (Mel 1992), coincidence detection (Larkum & Nevian 2008;Schiller & Schiller 2001), and directional selectivity (Smith et al 2013;. Importantly, the Ca 2+ influx associated with dendritic spikes plays a key role in modulating the plasticity of dendritic synapses (Gordon et al 2006;Sandler et al 2016;Gambino et al 2014;Villa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Very little connectivity data is currently available at this sub-dendrite scale, though several observations, taken together, suggest that withindendrite biases of this kind are biologically feasible: (1) the axonal projections of inhibitory neurons show famously strong spatial biases at the sub-dendrite scale (Bloss et al, 2016;DeFelipe, Ballesteros-Yáñez, Inda, & Muñoz, 2006;Karube, Kubota, & Kawaguchi, 2004;Tremblay et al, 2016); (2) excitatory pathways have well known spatial biases of other kinds, for example, they can selectively target dendrites in specific layers or parts of layers (Harris & Shepherd, 2015;J. S. Lund, 1988;Petreanu, Mao, Sternson, & Svoboda, 2009); (3) excitatory axons are subject to activity-dependent clustering, producing a tendency for co-activated axons to form contacts on nearby spines (DeBello et al, 2014;Iacaruso, Gasler, & Hofer, 2017;Lee, Soares, Thivierge, & Béïque, 2016;van Bommel & Mikhaylova, 2016Weber et al, 2016); (4) individual excitatory axons can show strongly biased projections at the sub-dendrite scale (Bloss et al, 2018;Morgan, Berger, Wetzel, & Lichtman, 2016) (5) proximal vs. distal synapses can be subject to different plasticity rules, which could lead to a spatial sorting-out of functionally distinct input pathways (Froemke, Poo, & Dan, 2005;Gordon, Gribble, Syrett, & Granato, 2012;Sandler, Shulman, & Schiller, 2016); and (6) differences in EPSP rise times suggest horizontal vs. vertical axons (Yoshimura et al, 2000) and near vs. far horizontal connections onto pyramidal neurons (Schnepel, Kumar, Zohar, Aertsen, & Boucsein, 2014) do, on average, terminate at different distances from the soma.…”
Section: Dendrites Provide a Parsimonious Neural Implementation Of Thmentioning
confidence: 99%